2019
DOI: 10.1039/c9ta09124f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-enzymatic fractionation to unlock the potential of biomass-derived carbon materials for sodium ion batteries

Abstract: Plant biomass, the most abundant and sustainable carbon source, offers a rich chemical space to design hard carbons for sodium ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 72 publications
2
50
0
Order By: Relevance
“…[151,152] M a X b materials provide the required "vacancies" for the insertion of Li + in the process of discharging. [153] The valence of a certain element in M a X b can be changed due to the Li + insertion and extraction process, while the structural [48,[78][79][80][81][82][83][84] The performance improvement diagrams of BDC-based materials in b) LIBs, [79,80,[85][86][87][88][89][90][91][92][93][94][95] c) SIBs, [8,81,[96][97][98][99][100][101][102][103] and d) KIBs [104][105][106][107][108][109][110][111][112][113] in recent years. e) Comparison of LIBs, SIBs, and KIBs.…”
Section: Alloying Reaction Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[151,152] M a X b materials provide the required "vacancies" for the insertion of Li + in the process of discharging. [153] The valence of a certain element in M a X b can be changed due to the Li + insertion and extraction process, while the structural [48,[78][79][80][81][82][83][84] The performance improvement diagrams of BDC-based materials in b) LIBs, [79,80,[85][86][87][88][89][90][91][92][93][94][95] c) SIBs, [8,81,[96][97][98][99][100][101][102][103] and d) KIBs [104][105][106][107][108][109][110][111][112][113] in recent years. e) Comparison of LIBs, SIBs, and KIBs.…”
Section: Alloying Reaction Electrode Materialsmentioning
confidence: 99%
“…[48,[78][79][80][81][82][83][84] Many studies have been reported by using BDC as an important part of batteries. [50][51][52][53][54][55][56][57][58][59][60] To better understand the research progress of BDC, we summarized the performance improvement diagrams of BDC-based materials in LIBs (Figure 1b), [79,80,[85][86][87][88][89][90][91][92][93][94][95] SIBs (Figure 1c) [8,81,[96][97][98][99][100][101][102][103] and KIBs (Figure 1d) [104][105][106][107][108]…”
Section: Introductionmentioning
confidence: 99%
“…[21] More recently,F eng et al proposed ap rocess to produce high-performance HC materials for SIBs by manipulating the componentsi nd ifferent plant biomasses. [150] They removed non-lignocellulose (such as proteins, minerals, and starch) andh emicellulose from three type of biomass, namely, brewer's spent grain, grape pomace, and walnuts hells, throughac hemical-enzymatic fractionation process in acid so-lution to product acidd etergent fibers (ADFs). The HCs derived from these ADFs all displayed excellent electrochemical properties.T he simultaneous absence of non-lignocellulose and hemicellulose led to expanded (002)i nterlayer spacing, which enhanced the specificc apacity remarkably.T his study provides afeasible methodt opreparebiomass carbon with high consistency.…”
Section: Challenges For Practical Applicationsmentioning
confidence: 99%
“…More recently, Feng et al. proposed a process to produce high‐performance HC materials for SIBs by manipulating the components in different plant biomasses . They removed non‐lignocellulose (such as proteins, minerals, and starch) and hemicellulose from three type of biomass, namely, brewer's spent grain, grape pomace, and walnut shells, through a chemical–enzymatic fractionation process in acid solution to product acid detergent fibers (ADFs).…”
Section: Challenges For Practical Applicationsmentioning
confidence: 99%
“…It's clearly seen from XPS survey spectrum that the sample contains four elements of C, Fe, Co, and Se (Figure S1). In the high‐resolution C 1s spectrum (Figure 4a), the peaks at 283.8 and 284.8 eV are indexed to the bonding energies of C−C and C−O, respectively [32] . In the XPS spectrum of Fe 2p (Figure 4b), the peaks at 706.8 and 719.3 eV are assigned to Fe 2p 3/2 and Fe 2p 1/2 spin orbits, respectively [33] .…”
Section: Resultsmentioning
confidence: 99%